Analisis Dampak Total Asset dan Pembiayaan Bank Syariah terhadap Pertumbuhan Ekonomi Indonesia: Analysis of the Impact of Total Assets and Sharia Bank Financing on Indonesia's Economic Growth - M. Wanri Wahyudin (Masyarakat Ekonomi Syariah Bogor, 2025)
This research examines the relationship between financing and total assets of Islamic banks on Indonesia's economic growth. The research results show that financing has a significant influence in supporting economic growth through increasing investment, consumption and business activity. Sharia banks play a role in strengthening strategic sectors such as infrastructure, education and health through long-term financing that is oriented towards sustainability. However, the effectiveness of sharia bank financing in encouraging economic growth is still influenced by the level of financial inclusion and supporting regulations. Apart from that, total assets of sharia banks also contribute to economic growth by reflecting banking capacity in channeling financing to productive sectors, such as MSMEs and industry. A financing model based on sharia principles that prioritizes risk-sharing provides an alternative for economic actors who experience limited access to conventional finance. The stability of Islamic banks in facing economic shocks helps strengthen the national financial system, which has a positive impact on economic growth. Thus, strengthening the sharia banking sector through education, supportive regulations, and the development of innovative financial products are key factors in optimizing its contribution to the Indonesian economy.Keywords: Author Guidelines; Journal Al-Kharaj; Article Templates